The Role of Islamic Banks in Tackling Financial Exclusion in North-East Nigeria - Tijjani Muhammad; Zanna Khalil (Türkiye İslam İktisadı Dergisi)
The purpose of this study is to explore the level of financial exclusion in North-East Nigeria and determine the reasons and barriers behind the huge percentage of financial exclusion. The contemporary Islamic bank is considered as a solution to tackle financial exclusion. The paper uses a quantitative approach in which 2500 questionnaires were distributed out of which 2352 were received back from the respondents. The data was gathered and analyzed using Structural Equation Modeling, and descriptive, correlation and regression analyses. The findings revealed that awareness, literacy, and religiosity are considered as the key barriers to financial exclusion and the need of Islamic banks with Shariah-compliant products is highly felt to address religious motivation in North East Nigeria. Since Islamic banks are compliant with Shariah principles, the Nigerian government should facilitate the creation of more Islamic banks to tackle financial exclusion.